2012
DOI: 10.1074/jbc.m111.325837
|View full text |Cite
|
Sign up to set email alerts
|

Single Point Mutation in Bin/Amphiphysin/Rvs (BAR) Sequence of Endophilin Impairs Dimerization, Membrane Shaping, and Src Homology 3 Domain-mediated Partnership

Abstract: Background:The BAR domain is a dimeric module controlling membrane curvature. Results: We identify leucine 215 involved in stabilizing the dimer interface and characterize the incidence of its substitution in SH3-mediated partnership in endophilins. Conclusion: Altered BAR conformation/rigidity impairs membrane binding, shaping, and partnership. Significance: This mutation in other BAR domain-containing proteins may unravel unanticipated functional relationships between the BAR domain and other structural unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
(57 reference statements)
3
24
0
Order By: Relevance
“…This hypothesis is supported by previous reports of low dimerization affinities for this protein (16,35,45,46).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This hypothesis is supported by previous reports of low dimerization affinities for this protein (16,35,45,46).…”
Section: Resultssupporting
confidence: 88%
“…Our finding of subnanomolar affinity rationalizes previous studies that are consistent with the predominance of N-BAR dimers over monomers at sub/low micromolar concentrations: distance measurements via EPR methods in solution at low micromolar concentrations (17), biochemical analysis of extracts from rat brain (71) and from cultured cells exogenously expressing endophilin A2 (45), and fluorescence microscopy analysis of endophilin A2 and A1 fluorescent protein chimeras in cultured cells (35). An analogous notion has been advanced for the BAR protein sorting nexin 9 (72).…”
Section: Discussionsupporting
confidence: 90%
“…Not as much is known about the dimers of endophilin III. The structural information indicates that endophilin III might have more conformational space to bind to other proteins such as dynamin [4][5][6][7] . [32] .…”
Section: Interactions Of Dynamin I With Endophilin I/ii/ Iiimentioning
confidence: 99%
“…Studies have shown that three types of endophilin exist in rats: endophilin I is expressed only in brain, endophilin II in multiple tissues, and endophilin III mainly in brain, testis and thymus [1][2][3] . Endophilins I and II also form dimers through a coiled-coil domain [4][5][6][7] . All three isoforms are concentrated in presynaptic nerve terminals [8][9][10] , and play important roles in synaptic vesicle recycling in neurons [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…BAR domains are found as dimers, and the importance of their dimerization is illustrated by experiments where dimerizationimpaired endophilin mutants are unable to bind and bend membranes (14,15). Both homodimerization and heterodimerization have been observed.…”
mentioning
confidence: 99%